Androgen-regulated MafB drives cell migration via MMP11-dependent extracellular matrix remodeling in mice - Mellissa C. Alcantara; Kentaro Suzuki; Alvin R. Acebedo; Daiki Kajioka; Satoshi Hirohata; Tsuneyasu Kaisho; Yu Hatano; Kazuo Yamagata; Satoru Takahashi; Gen Yamada (iScience, 2022)
Summary: While androgen is considered a pivotal regulator of sexually dimorphic development, it remains unclear how it orchestrates the differentiation of reproductive organs. Using external genitalia development as a model, we showed that androgen, through the transcription factor MafB, induced cell migration by remodeling the local extracellular matrix (ECM), leading to increased cell contractility and focal adhesion assembly. Furthermore, we identified the matrix metalloproteinase Mmp11 as a MafB target gene under androgen signaling. MMP11 remodels the local ECM environment by degrading Collagen VI (ColVI). The reduction of ColVI led to the fibrillar deposition of fibronectin in the MafB-expressing bilateral mesenchyme both in vivo and ex vivo. The ECM remodeling and development of migratory cell characteristics were lost in the MafB loss-of-function mice. These results demonstrate the requirement of mesenchymal-derived androgen signaling on ECM-dependent cell migration, providing insights into the regulatory cellular mechanisms underlying androgen-driven sexual differentiation.